Complications of splintage in congenital dislocation of the hip. Issue 11 (November 1991) - Langkamer, V G; Clarke, N M; Witherow, P
Abstract : The use of abduction splintage in the treatment of congenital dislocation of the hip has an important morbidity. Six children who developed complications are presented in this paper. Sustained splintage of an unreduced hip, overcorrection of the femoral head displacement, avascular necrosis of the femoral head, full thickness pressure sores, and excessive tibial torsion may occur as a consequence of treatment. Expert supervision of abduction splintage, correct case selection, and regular review are necessary to reduce the incidence of such complications.